The renovation of window mechanism for natural ventilation in a high-rise residential building. Issue 1 (2nd January 2018) - Lim, Hong Soo; Kim, Gon
ABSTRACT: The purpose of this paper is to analyse correlations between the amount of ventilation, building thermal loads and the operation of windows. The analysis was performed on a Korean high-rise residential building with small openable windows. As a result, polluted indoor air created by residents is not channelled to the outside appropriately due to the lack of natural ventilation. The building also experiences high cooling and heating load owing to the absence of a natural ventilation system. While conducting the analysis, the area of window opening was changed by positioning the window at different angles, and the cooling was analysed at those particular angles. Conclusively, to resolve the issue of building thermal loads as well as to be able to channel out polluted indoor air efficiently, operable windows should be installed at the upper part of the building, and window projection angles should be increased from 20˚ to 30˚.